2013
DOI: 10.1016/j.biocel.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and sarcopenia of aging: From signaling pathways to clinical trials

Abstract: Sarcopenia, the age-related loss of muscle mass and function, imposes a dramatic burden on individuals and society. The development of preventive and therapeutic strategies against sarcopenia is therefore perceived as an urgent need by health professionals and has instigated intensive research on the pathophysiology of this syndrome. The pathogenesis of sarcopenia is multifaceted and encompasses lifestyle habits, systemic factors (e.g., chronic inflammation and hormonal alterations), local environment perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
371
2
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 483 publications
(387 citation statements)
references
References 212 publications
(245 reference statements)
5
371
2
9
Order By: Relevance
“…56 Among these, collagen VI myopathies and Duchene muscular dystrophy (DMD) are the most studied. 57,58 Mitochondrial dysfunction in collagen VI dystrophies-Ulrich congenital muscular dystrophy and the less severe Bethlem myopathy-is characterized as a "latent" defect, which manifests as mitochondrial depolarization following oligomycin treatment. 57 The process of accumulation of abnormal mitochondria leading to apoptotic cell death is exacerbated by defective autophagy, and the reactivation of the autophagic flux rescues muscle degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Among these, collagen VI myopathies and Duchene muscular dystrophy (DMD) are the most studied. 57,58 Mitochondrial dysfunction in collagen VI dystrophies-Ulrich congenital muscular dystrophy and the less severe Bethlem myopathy-is characterized as a "latent" defect, which manifests as mitochondrial depolarization following oligomycin treatment. 57 The process of accumulation of abnormal mitochondria leading to apoptotic cell death is exacerbated by defective autophagy, and the reactivation of the autophagic flux rescues muscle degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the caspase-independent apoptosis is specific to skeletal muscle myonuclei, whereas other cells may undergo apoptosis through the more-classical caspase-dependent pathway. 76 While the contribution of caspase-dependent and independent pathways in aging human muscle has not been definitively established, 58 the expression levels of AIFM1 were elevated (by 10% to 25%) in muscle samples from older individuals, whereas the levels of CASP3 remained unchanged. 77 Activation of mitochondrial caspase-independent apoptotic signaling was also shown in aged rat gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed death causes the selective removal of individual targeted myonuclei and of 'myonuclear domains', the limited areas of cytoplasm that individual myonuclei support. 13,14 Muscle fiber segment with TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling)-positive nuclei alongside intact nuclei has been described. 15 Myonuclear apoptosis might contribute to skeletal muscle atrophy (however, see Bruusgaard et al 16 ).…”
Section: Unique Immune Privileges Of the Skeletal Musclementioning
confidence: 99%
“…Both apoptosis and autophagy possibly contribute to age-related sarcopenia that is associated with loss in the overall mass and with a reduced number of myofibers. 14,[21][22][23][24][25] Disorganization of myofibrils with Z line loss, mitochondrial swelling and sarcolemmal disruption are hallmarks of the skeletal muscle necrosis. Intracellular moieties including myoglobin, creatine phosphokinase (CK) and other sarcoplasm proteins are released into the bloodstream.…”
Section: Unique Immune Privileges Of the Skeletal Musclementioning
confidence: 99%